2020
DOI: 10.1016/j.cogdev.2020.100934
|View full text |Cite
|
Sign up to set email alerts
|

The effect of episodic future simulation and motivation on young children’s induced-state episodic foresight

Abstract: Highlights Examined the impact of episodic simulation and motivation on children’s episodic foresight Thirst was induced and children were asked to make future choices 3- to 5-year-olds completed the pretzel task under 4 different experimental conditions Children’s future predictions were most accurate in the motivation condition A novel and motivating food item, a cupcake, helped children overcome their current state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It is therefore possible that performance suffered more as the attractiveness and novelty of gaining stickers was gradually compromised as the task continued. As a result, motivation (to gain stickers) may decrease, which can influence children's future-oriented decision making [92]. We note that there was no significant order effect in Experiment 2, so perhaps children gained sufficient experience through Experiment 1 (experiencing both conditions) so testing order no longer influenced performance.…”
Section: Plos Onementioning
confidence: 80%
“…It is therefore possible that performance suffered more as the attractiveness and novelty of gaining stickers was gradually compromised as the task continued. As a result, motivation (to gain stickers) may decrease, which can influence children's future-oriented decision making [92]. We note that there was no significant order effect in Experiment 2, so perhaps children gained sufficient experience through Experiment 1 (experiencing both conditions) so testing order no longer influenced performance.…”
Section: Plos Onementioning
confidence: 80%
“…El primero de ellos consiste en los cambios metodológicos de aplicar cuestionarios y experimentos de forma online a través de aplicativos como Amazon Mechanical Turk (Gaesser et al, 2020) La evidencia científica hasta la fecha reporta que luego de realizar tareas de SE los participantes elevan su nivel de intención de ayuda (Gaesser et al, 2020); de igual forma, indica que entre más vivida sea la SE, más alto será el nivel de empatía afectiva (Vollberg et al, 2021) y, por tanto, se presentan conductas de ayudas entre grupos; sin embargo, en la presente investigación, aunque los resultados de SE indican que los escenarios de ayuda fueron vividos en un alto nivel y que los resultados de empatía evaluada con el IRI se encuentran correlacionados entre sí, no se presentan más conductas de ayuda si dichas variables se encuentran presentes dentro de un contexto de competencia. Otras investigaciones recientes indican que emplear SE en ambientes controlados dentro del laboratorio no logra inducir las respuestas esperadas (Mahy et al, 2020); por el contrario, imaginar la posibilidad de hacerle daño a otras personas cuando se considera moralmente justificado aumenta la probabilidad de que se realicen acciones que hieran al otro (Morris et al, 2022); esto, asociado a la alta identidad intragrupal, puede explicar por qué no se presentaron conductas de ayuda ni en los AC ni en los contextos neutros.…”
Section: Discussionunclassified
“…Second, future studies would also do well to include additional experimental conditions where adults make a preference choice for the present after thirst is induced to better determine the effect of the current state on present versus future reasoning (e.g., [ 4 ]), or make choices between water and a food item that differs from the food provided to induce thirst (i.e., pretzels) to rule out sensory-specific satiety (for review see [ 38 ]). For example, research has shown that when preschool children who have consumed pretzels to induce thirst are given the choice between water and a novel, more motivating food item (i.e., a cupcake), the majority of children choose a cupcake over water for both the future and the present [ 39 ]. Thus, the influence of the current state on preference choice may be dampened when a novel food item is presented.…”
Section: Discussionmentioning
confidence: 99%